Latest Pleistocene shrub expansion and steppe-tundra persistence in easternmost Beringia - Scott L. Cocker; Evan Francis; Ciara Wanket; Alistair J. Monteath; Svetlana Kuzmina; Diana Tirlea; Britta J.L. Jensen; Peter D. Heintzman; Beth Shapiro; Duane G. Froese (Quaternary Science Reviews, 2026)

Insect communities of late Pleistocene steppe–tundra and Holocene boreal forest ecosystems in central Yukon Territory, Canada - Scott L. Cocker; Svetlana Kuzmina; Nick Schafstall; Michael A. Monzon; Duane G. Froese (Journal of Quaternary Science, 2026)
Subfossil insect communities from the Quartz Creek site provide a detailed record of both Late Pleistocene steppe–tundra and Holocene boreal forest ecosystems in central Yukon Territory, Canada. Fifteen Pleistocene assemblages (marine isotope stages [MIS] 4 to 2) are dominated by steppe–tundra and dry‐tundra taxa, particularly the weevils Connatichela artemisiae and Lepidophorus lineaticollis , indicating a cold and dry environment with widespread Artemisia –grassland habitats. Periodic increases in mesic tundra, riparian and forest‐associated species reflect localised habitat mosaics within an otherwise arid landscape. Separated by a ~20 000‐year stratigraphic hiatus, the Holocene assemblages show a marked increase in taxa associated with shrubs, wetlands, and coniferous forests, including bark beetles such as Scolytus piceae , Polygraphus rufipennis, and Dendroctonus rufipennis , as well as the carpenter ant Camponotus herculeanus . These taxa indicate the presence of boreal forest habitats near the site by at least 6045 cal yr BP. Community composition and biodiversity indices show a clear difference between the Pleistocene and Holocene assemblages, reflecting a shift from relatively species‐poor steppe–tundra communities to more diverse assemblages associated with heterogeneous boreal forest environments. The continued absence of steppe–tundra specialists such as Connatichela artemisiae in our Holocene samples highlights the major restructuring of insect communities associated with the regional collapse of steppe–tundra ecosystems and the subsequent development of boreal forest environments in eastern Beringia.

Late Quaternary environmental change in eastern Beringia - Alistair J. Monteath; Mary E. Edwards; Duane Froese; Lesleigh Anderson; Benjamin V. Gaglioti; Scott L. Cocker; Julie Brigham-Grette; Matthew J. Wooller; Bruce Finney; Mark B. Abbott (Quaternary Science Reviews, 2025)